2006
DOI: 10.1002/acp.1254
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of pre‐trial publicity and jury deliberation on juror bias and source memory errors

Abstract: We examined the effects of exposure to pre-trial publicity (PTP) and jury deliberation on juror memory and decision making. Mock jurors either read news articles containing negative PTP or articles unrelated to the trial. They later viewed a videotaped murder trial, after which they either made collaborative group decisions about guilt or individual decisions. Finally, all participants independently attributed specific information as having been presented during the trial or in the news articles. Exposure to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
103
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(113 citation statements)
references
References 61 publications
8
103
2
Order By: Relevance
“…However, it is worth noting that, for a trial of this length, establishing a 30-minute deliberation period is a common practice (e.g. Kassin & Wrightsman, 1983;Ruva et al, 2007). Moreover, we found that the mean deliberation time used by jurors (M 018 minutes) fell far short of the time limit of 30 minutes.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…However, it is worth noting that, for a trial of this length, establishing a 30-minute deliberation period is a common practice (e.g. Kassin & Wrightsman, 1983;Ruva et al, 2007). Moreover, we found that the mean deliberation time used by jurors (M 018 minutes) fell far short of the time limit of 30 minutes.…”
mentioning
confidence: 82%
“…For example, Kramer, Kerr, & Carroll (1990) found that the effects of negative pretrial publicity on verdicts emerged only after deliberation. Similarly, Ruva, McEvoy, and Bryant (2007) found the effects of pretrial publicity increased following deliberation. London and Nunez (2000) found deliberation to temper jurors' tendency to rely on inadmissible evidence in the guilt judgments.…”
Section: Ecological Limitations To Investigations Of Pretrial Biases mentioning
confidence: 93%
See 1 more Smart Citation
“…guilt ratings (Ruva & McEvoy, 2008;Ruva et al, 2007). Ruva and McEvoy (2008) found that jurors exposed to PTP rated the prosecutor higher and the defense attorney lower on overall ability and likability than jurors not exposed to PTP.…”
Section: Mechanisms Responsible For Ptp Biasmentioning
confidence: 97%
“…Ruva et al (2007) found that mock jurors had good memory for both PTP and trial information, but with high confidence believed that the PTP information was also presented at trial. These critical SM errors mediated the effect of PTP on guilt ratings.…”
Section: Source Memorymentioning
confidence: 97%